Construction of nested real ideal lattices for interference channel coding - Trinca Watanabe, C. C. (2019)
In this work we develop a new algebraic methodology which quantizes real-valued channels in order to realize interference alignment (IA) onto a real ideal lattice. Also we make use of the minimum mean square error (MMSE) criterion to estimate real-valued channels contaminated by additive Gaussian noise.